PENGARUH JENIS PUPUK ORGANIK DAN PENJARANGAN BAKAL BUAH TERHADAP PERTUMBUHAN DAN HASIL MELON - Ari Nursyamsi; Nasrudin Nasrudin; Siti Nurhidayah (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2023)
Utilization of organic matter as a plant nutrition can be used to increase the growth and yield of melon cultivation. Fruit thinning treatment can be used to improving fruit quality. This study aims to examine the effect of various organic fertilizers and fruit thinning on the growth and yield of melons. The study was conducted in Screen house Universitas Perjuangan Tasikmalaya from March to June 2021. The study used a factorial completely randomized design. First factor is type organic fertilizer consist of solid chicken manure, vegetable waste liquid fertilizer, and cow urine. Second factor is fruit thinning consist of 1 and 2 remaining ovules. Based on the research results, the interaction of vegetable waste with the remaining 1 ovule resulted in the highest number of leaves compared to other interactions. Chicken manure and vegetable waste with 1 and vegetable waste with 2 ovules produced the greenest leaves compared to other interactions. The application of organic fertilizer had no significant effect on plant biomass, root length, fruit diameter, fruit thickness, total dissolved solids, and productivity. Fruit thinning significantly affected to plant biomass, root length, fruit diameter, fruit thickness, fruit weight per plant, and productivity. 1 ovule was the best treatment compared to 2 ovules. Provision of vegetable waste with 1 and 2 ovules affects the growth and yield of melon plants. Fruit thinning by leaving 1 ovule effectively to growth and yield of melons.